Informal Ways and Means, in Competition with Formal Patterns, in Modern Turkey (Global Journal of Management and Business Research, 2016)
Turkey, is undergoing a fast modernization process on one hand; but people still cling to traditional ways, on the other hand. This dual character makes it difficult for the formal and informal aspects of social life to go in parallel. There is a gap between anything officially on paper and the actual social reality of the real world out there.
Keywords: tradition; traditional; formal; informal; modern